Sepsis caused by emphysematous pyelonephritis: A case report - Yang, Zheng; Li, Zhihui (Frontiers in Medicine, 2023)
Purpose Emphysematous pyelonephritis (EPN) is a rare, life-threatening necrotizing renal parenchymal infection. It is most commonly reported in patients with poor glycemic control. Patient concerns We report the case of a 64-year-old woman who presented to the emergency room with fever and weakness over the last few days. Diagnosis After a series of tests in the diagnostic workup, the patient was diagnosed with emphysematous pyelonephritis and sepsis. Intervention and outcome She received conservative treatment with meropenem and symptomatic treatment, and the symptoms improved significantly. Lessons EPN can be reliably diagnosed using non-contrast abdominal CT imaging. The infection is most commonly caused by the Escherichia coli species, and a good curative effect can be achieved with early diagnosis and appropriate and timely treatment.